Analisis Kinerja Pegawai Kantor Desa Sukorame Kabupaten Lamongan Dalam Memberikan Pelayanan Kepada Masyarakat - Aprilia, Avista Ade; Fadhli, Khotim (Blantika: Multidisciplinary Journal, 2025)
This study aims to analyze the performance of employees at the Sukorame Village Office in providing services to the community, using five main indicators: work quality, timeliness, initiative, capability, and communication. The method used in this study is qualitative, with data collection techniques through interviews, observations, and documentation. The results show that the overall work quality of the employees is quite good, especially in terms of responsiveness to community needs. However, there are challenges regarding discipline and mastery of technology that still need to be improved. In terms of timeliness, although there is a commitment to provide on-time services, limitations in resources and the absence of certain officials have caused some services to not be completed as scheduled. Employee initiatives to improve service quality are still assessed to be low, thus requiring motivation and reinforcement of a proactive work culture. The technical abilities of employees are mostly adequate, but some employees have not fully mastered administrative tools, such as computers. Employee communication with the public is considered quite good, with the delivery of information being clear, polite, and effective. This study concludes that although the performance of employees at the Sukorame Village Office is already quite good, there are still several aspects that need improvement, particularly in discipline, initiative, and technical abilities. Recommendations include enhancing employee training, strengthening supervision, and establishing a more professional work culture to improve overall service quality.